2017
DOI: 10.1007/s12272-017-0986-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gut microbiota on drug metabolism: an update for safe and effective use of drugs

Abstract: The intestinal mucosa and liver have long been considered as the main sites of drug metabolism, and the contribution of gut microbiota to drug metabolism has been under-estimated. However, it is now generally accepted that the gut microbiota plays an important role in drug metabolism prior to drug absorption or during enterohepatic circulation via various microbial enzymatic reactions in the intestine. Moreover, some drugs are metabolized by gut microbiota to specific metabolite(s) that cannot be formed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 59 publications
0
38
0
2
Order By: Relevance
“…The gut microbiota is affected by drug dosages, pharmaceutical compositions, length of treatment course, and adjuvant use (Noh et al., 2017). At the same time, the changes in the gut microbiota may change the pharmacokinetic characteristics of the therapeutic drug.…”
Section: Resultsmentioning
confidence: 99%
“…The gut microbiota is affected by drug dosages, pharmaceutical compositions, length of treatment course, and adjuvant use (Noh et al., 2017). At the same time, the changes in the gut microbiota may change the pharmacokinetic characteristics of the therapeutic drug.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, p ‐cresol, an endogenous microbial metabolite, undergoes sulfation and can diminish APAP sulfation by competitive inhibition . Finally, Hendrickson et al reported that APAP can undergo enterohepatic circulation, whereby APAP‐gluc is deconjugated by microbial‐expressed β‐glucuronidase prior to reabsorption . Disrupting enterohepatic circulation can lead to decreases in APAP half‐life, resulting in lower APAP exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no such phenomenon was observed in any of the concentration–time profiles in the present study in rats, which might point to species-related differences in metabolism and excretion routes. Among other factors, the impact of enterohepatic circulation of a drug on its plasma concentration depends on rate and extent of breakdown of glucuronidated or otherwise conjugated compound by intestinal microbiota [ 28 ]. Substantial compositional diversity of the gut microbiota has been reported previously [ 29 ].…”
Section: Discussionmentioning
confidence: 99%